PENGEMBANGAN PERSAMAAN KORELASI PENDIDHAN KOLAM UNTUK REFRIGERAN HIDROKARBON - Pasek, Ari Darmawan; Adriansyah, Willy; Hery, Hery; Leo, Hengky (Mesin, 2008)
Hydrocarbons (HC) are considered as the alterative substitutes of CFC and HCFC refrigerants. Using it as new refrigerants needs a complete knowledge of its characteristics. One of them is the boiling heat transfer coefficient. Series of experiments were carried out to investigate this characteristics. Experiments had been carried out with R-12 (CFC) and R-22 (HCFC) and their substitutes, HC-12 and HC-22. Tested refrigerant was conditiond at a saturated state and an electric heater immersed in the refrigerant pool of liquid was used as the boiling surface. Boiling heat transfer coefficient is determined as the ratio between the heat flux and the excess temperature on the boiling surface. The experimental results were compared between R-12 and R-22 with their substitutes. The experimental results were compared with the correlation equations proposed by researchers. Based on the analysis results, modified correlation equations are proposed for the tested refrigerants.